Processing of self-relevant information - Korn, Christoph W. (2013)
People constantly receive self-relevant information. For example, social interaction partners give feedback on character traits (e.g., by telling you that you are polite, tidy, or superficial) and media provide statistical information about the likelihood of experiencing future life events (e.g., by stating the likelihood of living past the age of 80 or getting caner). However, the potential behavioral and neural components of self-relevant information processing are underexplored. In this thesis, I aim at providing the empirical basis for a neurocognitive model of self-relevant information processing. I draw on behavioral research on the self-concept, the social self, and self-related positivity biases as well as on neuroscientific research on the neural processes related to self-judgments, reward, and mentalizing. Study 1 used behavioral measures and functional magnetic resonance imaging (fMRI) to test how social feedback on character traits changed participants’ self-ratings. This social feedback was given by peers within the context of a face-to-face interaction. Study 2 extended the approach of study 1 to a cultural comparison between participants of German and Chinese background. Study 3 investigated potential implications of self- relevant information processing for psychiatry by testing how depressive patients updated their personal estimates of the likelihood of future life events when receiving statistical information about these events. Healthy participants processed self-relevant information in a positively biased way, i.e., they updated their self-ratings and their estimates of the future more after receiving desirable than after receiving undesirable information. In contrast, positively biased updating about future life events was absent in depressive patients. Culture modulated social conformity, i.e., Chinese participants relied more on social feedback than German participants. Self- relevant information processing comprised a reward component that correlated with neural activity in the ventral striatum and the anterior cingulate cortex/medial prefrontal cortex (ACC/MPFC) and a social comparison component that correlated with neural activity in the mentalizing network including the MPFC, the temporo-parietal junction (TPJ), the superior temporal sulcus (STS), the temporal pole (TP), the inferior frontal gyrus (IFG), and the pre- supplementary motor area (preSMA). Self-related MPFC activity differed between German and Chinese participants. In conclusion, this dissertation advances the understanding of self-relevant information processing by combining behavioral research on the self-concept, the social self, and self-related positivity biases with neuroscientific research on reward and mentalizing. The proposed neurocognitve model integrates research on the cultural diversity of human societies, offers a framework for a better understanding of psychiatric disorders, and lends itself to a future adaptation to computational modeling approaches.
Keywords: Hochschulschrift